Good Faith in Construction Contract: A Common Law Perspective - Abdullah, Nurhidayah; Ong , Tze Chin; Nasir, Nur Atiqah; Kurniawan, Faizal (International Journal of Sustainable Construction Engineering and Technology, 2023)
The good faith principle requires contracting parties to be honest as well as considering their contracting partners in performing their contractual duties. In the event, contract clauses are insufficient to protect the interests of the innocent party in a breached contract, the said innocent party may rely on the good faith principle to ensure the fair. However, applying good faith principles to construction contracts is a difficult task. By nature, construction contracts are unique due to the fact that parties (Client and Contractor) are presumed competent to carry out their parts of the contractual obligations. Controversially, the construction contract is often unfairly prejudicial as the Client would customarily have the upper hand in deciding the terms and conditions of a contract. It is the objective of the research to examine the relevancy of application of good faith principle in construction contracts by employing qualitative content analysis. This study adopts a qualitative research approach, mainly employing library and internet resources with the intention to explore relevant legislation, textbooks, journals, research papers and articles. The comparative approach in this paper used content analysis from primary and secondary legal resources of different jurisdictions in the United Kingdom, Malaysia and Australia to compare the application of the good faith principle in the context of construction contracts.  The findings of the research reveals that the adoption and application of the good faith principle in construction contracts is of limited usage even though it is widely used in general contract law of United Kingdom, Malaysia and Australia. This article contributes to the knowledge of the good faith principle in construction contracts, particularly with standard form contracts, by highlighting the importance of the good faith principle in achieving a fairer functioning of construction contracts in its application.